Cost-benefit analysis of energy efficiency system for homes and buildings - Zheng, Xi (2015)
Energy efficiency system, often incorporating efficient cooling, lighting and other clean energy technologies, is an innovative approach to reduce energy consumption in the provision of a given good or service. This report focuses on the development of a cost-benefit analysis model, which is used to conduct a primary cost-benefit analysis for the desired energy efficiency implementation, in LabVIEW environment. Between the two cases of Homes and Buildings, the latter one is primarily meant to be small offices in this project; Algorithms are devised to be applied accommodate both with little alternation on the input data. To be more specific, the model includes three main components namely ‘Air-conditioner’, ‘Lighting’ and ‘Other Appliances’ to conduct accurate analysis under each sector. A ‘Financial Analysis’- module is also included to generate an overview of the entire energy efficiency implementation. This new development possesses appealing user interface, RETScreen-compliant algorithms and easy-to-update reference data module, compared with previous initiatives developed by other students. In short, this development is able to perform insightful analysis on energy efficiency system from a home owner’s perspective.